2016
DOI: 10.3738/1982.2278.1640
|View full text |Cite
|
Sign up to set email alerts
|

MÉTODOS DE SOMA TÉRMICA NA DETERMINAÇÃO DE PLASTOCRONO DE Helianthus annuus L. CULTIVADO EM AMBIENTE PROTEGIDO EM CAPITÃO POÇO-PA

Abstract: RESUMO:A temperatura do ar é um dos principais parâmetros agrometeorológico que afeta a fenologia das culturas agrícolas, por está principalmente relacionada a taxa de fotossíntese, afetando também o plastocrono. Com isso, esse fato tem motivado a realização de inúmeros trabalhos sobre este fenômeno, utilizando-se diversos métodos para a mensuração e estimativa desta influência. Objetivou-se com este trabalho avaliar os métodos de determinação de graus-dia para estimação do plastocrono em duas cultivares de gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…However, it is evident that the minimum temperature that lisianthus cultivars require for their adequate development is 13.9ºC, to maintain a minimum development. According to Souza et al (2016), it can be inferred that, below this value, the species has its development inhibited or considered negligible, mainly in times of low temperatures and lower solar radiation, as it occurs in the autumn/winter season in the southern region of Brazil.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is evident that the minimum temperature that lisianthus cultivars require for their adequate development is 13.9ºC, to maintain a minimum development. According to Souza et al (2016), it can be inferred that, below this value, the species has its development inhibited or considered negligible, mainly in times of low temperatures and lower solar radiation, as it occurs in the autumn/winter season in the southern region of Brazil.…”
Section: Resultsmentioning
confidence: 99%
“…According to Souza et al (2016), the thermal time is an attractive and widely used method to represent biological time in plants. Studies on the thermal time were developed in many crops (Bartz et al, 2017;Carvalho et al, 2014;Deprá et al, 2016;Miranda and Junior, 2010;Lucas et al, 2015;Paula et al, 2005;Steinmetz et al, 2017;Tomazetti et al, 2015;Trentin et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Sentelhas and Ungaro (1998) assessed bioclimatic indexes of sunflower crop and concluded that the thermal time presented the lowest total variability in comparison to other indexes, being deployed to study the phenology of Brazilian sunflower cultivars. Other researches were also developed based on thermal time in sunflower (Lucas et al, 2015, Souza et al, 2016, potato (Paula et al, 2005), watermelon (Trentin et al 2008), maize (Deprá et al, 2016), common bean (Miranda and Junior, 2010), rice (Bartz et al, 2017, Steinmetz et al, 2017, grapevine (Tomazetti et al, 2015), and coffee (Carvalho et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Of the studies on the influence of air temperature and the photoperiod on plant growth, most have been carried out on agricultural crops, like strawberry (Tazzo et al 2015), sunflower (Souza et al 2016), rice (Steinmetz et al 2017), potato (Bisognin et al 2017), grape (Pedro Júnior and Hernandes 2018), lettuce (Tezza and Minuzzi 2019), and arugula (Barreiros et al 2021) and focused on germination, seedling establishment, budding, flowering, fruiting, and ripening. However, studies of this nature on tropical forest species are still scarce and have focused only on those of commercial interest, such as Eucalyptus at the seedling Freitas and Martins 2019) and flowering stages (Rawal et al 2015), and some Brazilian forest species at the germination (Daibes et al 2019) and seedling stages (Martins et al 2022c).…”
Section: Introductionmentioning
confidence: 99%